2020
DOI: 10.3390/s20247143
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Inertial Sensors for Gait Analysis in Adults with Osteoarthritis—A Scoping Review

Abstract: Our objective was to conduct a scoping review which summarizes the growing body of literature using wearable inertial sensors for gait analysis in lower limb osteoarthritis. We searched six databases using predetermined search terms which highlighted the broad areas of inertial sensors, gait, and osteoarthritis. Two authors independently conducted title and abstract reviews, followed by two authors independently completing full-text screenings. Study quality was also assessed by two independent raters and data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 108 publications
4
60
0
Order By: Relevance
“…Variability in the study designs reported represents the variety of the context that wearable technology was used in. Most studies recruited relatively young participants (62–66 years of age) and in the overweight/obese BMI category (28–32 kg/m 2 ), which is in line with a review by Kobsar et al [ 8 ], but questions the generalizability of the results to older populations with a more severe OA stage. We did not collect data on radiological severity of knee OA, which could have provided more insights regarding the generalizability of the results to people with a more severe knee OA diseases stage and thus can be a topic for future research.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Variability in the study designs reported represents the variety of the context that wearable technology was used in. Most studies recruited relatively young participants (62–66 years of age) and in the overweight/obese BMI category (28–32 kg/m 2 ), which is in line with a review by Kobsar et al [ 8 ], but questions the generalizability of the results to older populations with a more severe OA stage. We did not collect data on radiological severity of knee OA, which could have provided more insights regarding the generalizability of the results to people with a more severe knee OA diseases stage and thus can be a topic for future research.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, the COVID-19 pandemic has had a notable impact on primary care services which have had to adapt to different methods of service provision to limit the number of face-to-face appointments with patients [ 7 ]. Concurrently, there has been a rise in the research and development of wearable technology for healthcare applications for this population [ 8 , 9 ], which could facilitate the treatment and monitoring of patients outside of a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A representative subset of these wearables is summarized in Table 1. A more thorough review of wearable sensors for gait monitoring can be found in [15,27,28]. A vast majority of these wearables make use of a gyroscope (for measuring angular velocity and orientation), accelerometer, or inertial measurement unit (IMU-which combines a multi-axis gyroscope and accelerometer and may also include a magnetometer) and are worn on the foot (shoe).…”
Section: Gait Monitoring Technologiesmentioning
confidence: 99%
“…Alternatively, Inertial Measurement Units (IMUs) bear the advantage of easy mounting to the patients without the restriction or complexity of a gait lab [12] and a scoping review by Kobsar et al (2020) demonstrated the increased popularity of using wearable technology for (mostly spatio-temporal) gait analysis in people with OA [13]. Alternatively, an IMU at the lower trunk level was used as an easy and unobtrusive method to assess gait and running biomechanics, both in healthy adults and patients with neuromuscular disorders [12].…”
mentioning
confidence: 99%